Metabolic changes in local and systemic cowpea [Vigna unguiculata (L.) Walp.] leaves induced by cowpea severe mosaic virus infection - Bret, Raissa Souza Caminha (2023)
The susceptibility of plants to diseases is a complex phenomenon and regulated by specific mechanisms for recognition of the pathogen and signalling responses within the cell, which culminate in a compatible or incompatible interaction between the pathogen and the plant. Despite the importance in understanding the mechanisms by which plants can tolerate a pathogen attack, the knowledge of the genetic and biochemical factors that are involved in the plant-pathogen interaction is still scarce. Furthermore, although the molecular mechanisms for virus perception are relatively well-documented, the metabolic responses to viral infection remain poorly understood, especially in cowpea (Vigna unguiculata (L.) Walp.) in which the metabolic responses to virus infection has not been investigated yet. Cowpea is an important staple food for dry regions, but virus infection can decrease yield by up to 85%, representing a major bottleneck for cowpea cultivation. Here, we aimed to investigate the metabolic responses of macaibo (resistant) and pitiuba (susceptible) cowpea genotypes to infection caused by cowpea severe mosaic virus (CPSMV). An extensive metabolic characterization was performed using leaves directly infected with CPSMV (local leaves) and those from the same trifoliate (systemic leaves), aiming to identify how CPSMV infection influences the metabolism of directly infected leaves and those adjacent to the site of infection. Metabolomics analyses were performed using gas and liquid chromatography coupled to mass spectrometers (GC-MS, LC-MS) for metabolite profiling analysis of primary metabolites and metabolic fingerprinting analysis of secondary metabolites, respectively. Our results showed that the metabolism of local leaves is substantially altered by CPSMV infection at primary metabolism level, even in the resistant (macaibo) genotype. Notably, CPSMV infection altered the dynamic of primary metabolites in macaibo leaves, which results in a new metabolic homeostasis but maintain the stability of both the primary metabolic network and the level of secondary metabolites. We further showed that the metabolism of macaibo and pitiuba leaves differ substantially even in the absence of CPSMV infection. Beyond providing unprecedented important information on the metabolic responses of cowpea plants to CPSMV infection, our results collectively highlight that the metabolic responses to CPSMV infection differ substantially between resistant and susceptible cowpea genotypes, in which a higher constitutive metabolic flux toward shikimate is observed in macaibo, when compared to pitiuba, and a lower metabolic fluxes from pyruvate to the TCA cycle is observed upon CPMSV infection in macaibo